e-Scientific Calculator / Liew Chee Kit - Liew , Chee Kit (2002)
This report is to specify the development of a software-based scientific calculator named eSciCalc. It is a standalone application running on the Microsoft Windows platform. There are nine chapters in this report.The first chapter is the introduction to the project. Information of the project related to its background, motivation, problem definition, objective to achieve, project scope, expected outcome, and the proposed schedule is provided in this chapter. The second chapter will present the result of literature review performed. The review on existing calculator and development tools are included here. The third chapter will describe the development approach taken for this project. The strength of the approach is also included.The fourth chapter states the result of requirements capture and analysis. The requirements are captured as use cases and the flow of even for each use case is included. In analysis, use case realisation in form of analysis classes is provided for each use case using collaboration diagrams and textual flow of event. The fifth chapter wilt specify the software design. This chapter includes the use case realisation in term of design classes for each use case with a sequence diagram and textual flow of event. Chapter six states the implementation approach employed in the project. Chapter seven states the test model use in this project. This chapter include the test case and the test procedure that use to test the software. Chapter eight states the evaluation of this project. This chapter include the strength, limitation and future enhancements of the software. Chapter nine states the conclusion. Which include the problems and solutions, knowledge gained and projects conclusion.